Microvariation in syntactic doubling - Barbiers, Sjef, 1959-; Koeneman, Olaf; Lekakou, Marika; Ham, Margreet van der (Syntax and semantics ;, 2008)
Syntactic doubling is the phenomenon in which a constituent, i.e., a morphosyntactic feature, morpheme, word or phrase, is expressed two or more times within a clause. Since such duplicates are often redundant in that they do not contribute to semantic interpretation, the question arises as to why they are possible or necessary. This theoretical question becomes even more urgent in view of the fact that closely related language varieties such as the dialects of one dialect family often differ with respect to the possibility of doubling. This book puts together seventeen papers on microvariation in syntactic doubling that deal with such theoretical issues. They provide a rich overview of the syntactic doubling phenomena attested so far and of the theoretical analyses that are currently available. The syntactic doubling phenomena discussed include, among others, subject pronoun doubling, WH pronoun doubling, possessive pronoun doubling, clitic doubling, expletive subjects, tense, mood and aspect doubling, auxiliary doubling, preposition doubling and negation doubling. Language varieties discussed in this book include Afrikaans, Alemannic, Bavarian, Tyrolean German, dialects of Dutch, dialects of Swedish, Norwegian, Danish and Faroese, colloquial Icelandic, colloquial Finnish, colloquial European and Brazilian Portuguese, Catalan, Argentinian Spanish, dialects of Italian, Rumanian, Albanian, Bulgarian, Serbo-Croatian, Pontic, Macedonian and Modern Greek.